AB1381 Four annual international different meetings of rheumatology: comparation of the contents, analysis, challenge and oportunities. (12th June 2018) - Pedro, A.J.; Cuevas, E.; Abud, C.; Moreno, R.; Martinez, M.; Herrera, D.; Acevedo, E.; Lopez, H.; Ramos, D.; Aguilera Barragan, G.; Martinez, G.; Luna, T.; et al.
Abstract : Background: The medical meetings are a tool to help us be able to escalate and actualize the medical knowledge and their quality is a responsibility of Colleges and Institutions. Objectives: To assess the academic level of four types of different annual Meeting of Rheumatology Methods: We used as support information the summaries published in the supplements of the journal Reumatologia Clinica, SE1 Vol. 12 of February 2016, the supplement SE 1 Vol. 13 of February 2017, the application for electronic media of the ACR/ ARHP 2016 of the American Congress of Rheumatology 2016 and the website for abstracts of, EULAR 2017 dedicated to the surveys presented in the XLIV Mexican Congress of Rheumatology, XLV Mexican Congress of Rheumatology and the 2016 ACR/ ARHP Annual Meeting, and EULAR 2017 respectively, of each survey we was obtained information about of the diverse pathologies, the type of trial, content and population referred (adults versus children). Results: 275, 340, 3275 and 4129 were presented in the XLIV Mexican Congress of Rheumatology, XLV Mexican Congress of Rheumatology, the 2016 ACR/ ARHP Annual Meeting and EULAR 2017 respectively. Rheumatoid arthritis (RA) was the most common pathology with 23%, 26%, 21% and 27% in CMR 44, CMR 45, ACR 2016 and EULAR 2017 respectively, followed by systemic lupus erythematosus, third place was vasculitis, beside in international congress was the spondyloartrhitis. Highlighted, RA the items about of clinic manifestations were accounted for almost 30% in the Mexican congress and almost 20% in ACR and EULAR. Observational studies accounted for almost 40% in Mexican congresses vs. 33% in ACR 2016 and 55% in, EULAR 2017 beside surveys about of basic research were minimal in Mexican congress, but in ACR 2016 accounted for 21% and 12% in . EULAR 2016 The trials about of Paediatric Rheumatology were 12.3%, 5.5% and 4.9% in CMR 44, CMR 45 and ACR 2016 respectively. Conclusions: Rheumatology Meeting constitutes a support to obtain the adequate medical knowledge based in evidence, in this important branch of Medicine. We require of the collaborative efforts to achieve best goals with controlled studies, clinical and basic assays, increasing the Meeting's quality. References: [1] Serrano KJ, Yu M, Riley WT, Patel V, Hughes P, Marchesini K, Atienza AA. Willingness to Exchange Health Information via Mobile Devices: Findings From a Population-Based Survey. Ann Fam Med. 2016Jan-Feb;14(1):34–40. doi: 10.1370/afm.1888. [2] Studdert DM, Mello MM, Gawande AA; Ghandi TK, Kachalia A, Yoon C, et al. Claims, Errors, and Compensation Payments in Medical Malpractice Litigation. N Engl J Med2006;354:2024–33. [3] Bothwell LE, Greene JA, Podolsky SH, and Jones DS. Assessing the Gold Standard—Lessons from the History of RCTs. N Engl J Med2016; 374:2175–81. [4] Fiore LD and Lavori PW. Integrating Randomized Comparative Effectiveness Research with Patient Care. N Engl J Med2016; 374:2152–8. Disclosure of Interest: None declared